Creating brand market value - Brzaković, Aleksandar; Brzaković, Tomislav; Brzaković, Pavle (Anali Ekonomskog fakulteta u Subotici, 2020)
The brand represents valuable intangible assets and one of the most important resources that offers a number of benefits and therefore the brand must be constantly built and carefully managed. Through marketing efforts, companies try to create a strong and recognizable brand, which is actually something that exists in the minds of customers. Creation of a brand implies a number of activities: designing the brand elements, a unique trademark, characteristic propaganda messages and other activities aimed to position the brand on the market. The process of creating the market value of a brand aims to maximize the value of the brand itself. The three most important models in the brand planning and creating process are: brand positioning model, brand resonance model and brand value chain model.